ANALYSIS OF IODINE CONTENT IN SEAWEED AND ESTIMATION OF IODINE INTAKE - Nur Qadri Rasyid (Marina Chimica Acta, 2017)
ABSTRACTSeaweed has become food the most popular in many Asian countries because apart from has a distinctive taste, seaweeds having the mineral content needed by the body. Seaweed iodine containing minerals being obtained from sea water, who was one of micro nonmetallic minerals which is very much needed by the body. Lack of iodine can cause cretinism, hyacinth, and the production of hormone low ( hypothyroidism due to enlargement the thyroid gland. Excess intake iodine also can cause an impairment of health. Recommendations intake iodine per day of by 0.15 mg/day. The purpose of this research to know the iodine on seaweed (seaweed ) in the village Punaga sub district Mangarabombang district Takalar. The kind of research laboratory this is a observation to technique quantitative analysis. Technique the sample collection in purposive sampling as many as 5 samples. Next sample each in destructor dry then examined in of the spectrophotometer Uv-visible at wavelengths 463,9 nm. Based on research results obtained levels of iodine on seaweed (seaweed ) are 1.72 µg/g, 1.92 µg/g, 1.73 µg/g, 1.94 µg/g, and 1.89 µg/g it shows that seaweed has any iodine high.